Đorđe Maletić’s Contributions to the Aesthetics of Acting - Savković, Nemanja V. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
The paper examines the contribution of Đorđe Maletić to the aesthetics of acting. Maletić was a prominent figure in Serbian theater life in the second half of the 19th century, but recently he has been unjustifiably relegated to the margins of domestic theater historiography and theatrology. First, his general aesthetic views are presented, in which he relied eclectically on various sources, mainly on Lessing, Schiller, and Hegel. Subsequently, his thoughts on acting and acting creativity, present in various writings published in the period from 1847 to 1884, are presented and interpreted. Considering these findings, it emerges that Maletić was not only a transmitter of European theatrical achievements into the cultural environment of Serbia but also that he showed a high level of independence in thinking about theater and dramatic art, especially in thinking about the phenomenon of acting. His characterization of the actor as “incarnated beauty, the idea of the beautiful, assumed physicality”, who manifests the idea of beauty “on himself, so that he is both a thought and a material for the expression of thoughts, he both acts and is acted upon” — represents the most complete aesthetic interpretation of acting and acting creativity that we can find in the history of Serbian theater thought of the 19th century
Keywords: Đorđe Maletić; acting; acting creativity; aesthetics of acting; theatrology